PENGARUH KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWANPADA PT ASURANSI JIWASRAYA GORONTALO - Zuchri Abdussamad (Jurnal Manajemen., 2014)
These results indicate that: 1) Increased labor productivity through compensation on PT. BNI Life Insurance Gorontalo simultaneously significant effect on the productivity of employees working koofiensi shown derterminasi r2 = 0.512, or by 51.2% and the remaining 48.8% is influenced by other factors; 2) Increased productivity of employees through compensation have a significant effect on the productivity of the employees indicated by (t = 6.061). This is indicated by the regression results where the value of β 0.578 These results indicate that with the right policies and the compensation received by the employee, the employee will improve the performance of PT. BNI (Persero) Gorontalo.